Resposta óptica de sistemas atômicos no espaço livre ou aprisionados dentro de cavidades ópticas no regime de armadilhamento coerente de populações - Oliveira, Murilo Henrique de (Universidade Federal de São Carlos, 2018)
The aim of this work is to study the electromagnetically induced transparency (EIT) and the coherent population trapping (CPT) phenomena in three-level systems, such as atoms and quantum dot molecules (QDM). The present work can be basically divided into two parts. The first one focus on comparing and explaining the differences between the optical reponses of systems composed by atoms and QDM and on proposing a possible application in cavity linewidth narrowing. In the second part, we turn our attention to the study of controlable optical bistability in three-level systems in the regime of CPT, bringing new perspectives to the study of these bistable systems and some practical applications as well.
Optical response of atomic systems in free space or trapped inside optical cavities in the coherent population trapping regime
Keywords: Interação radiação-matéria; Transparência eletromagneticamente induzida; Aprisionamento coerente de populações; Moléculas de pontos quânticos; Cavidades ópticas; Biestabilidade óptica; Radiation-matter interaction; Electromagnetically Induced Transparency; Coherent Population Trapping; Quantum dot molecules; Optical cavities; Optical bistability; CIENCIAS EXATAS E DA TERRA::FISICA